Dynamics of charged particles and their radiation field - Spohn, Herbert, 1946- (Cambridge University Press, 2004)
This book provides a self-contained and systematic introduction to classical electron theory and nonrelativistic quantum electrodynamics. It covers the interaction between charges and the Maxwell field, with emphasis on radiation phenomena and relaxation to the ground state, space-adiabatic limit, effective mass and g-factor, and removal of the ultraviolet cut-off.